2019
DOI: 10.1016/j.bja.2018.10.061
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of perioperative complications in paediatric cranial vault reconstruction surgery: a multicentre observational study from the Pediatric Craniofacial Collaborative Group

Abstract: Background: The current incidence of major complications in paediatric craniofacial surgery in North America has not been accurately defined. In this report, the Pediatric Craniofacial Collaborative Group evaluates the incidence and determines the independent predictors of major perioperative complications using a multicentre database. Methods: The Pediatric Craniofacial Surgery Perioperative Registry was queried for subjects undergoing complex cranial vault reconstruction surgery over a 5-year period. Major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
(13 reference statements)
1
17
0
Order By: Relevance
“…Bleeding and blood transfusion were commonly seen in children undergoing cardiac, craniosynostosis and scoliosis surgeries (24)(25)(26). The necessary RBC transfusion requirements heightens the risk of transmission of several infectious diseases (27), and seriously burdens hospitals and patients financially.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding and blood transfusion were commonly seen in children undergoing cardiac, craniosynostosis and scoliosis surgeries (24)(25)(26). The necessary RBC transfusion requirements heightens the risk of transmission of several infectious diseases (27), and seriously burdens hospitals and patients financially.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent multicenter study by the pediatric craniofacial collaborative group reported a 15% complication rate. 2 Despite this relatively high complication rate, there was no in-hospital mortality for patients undergoing cranial vault reconstruction surgery. This supports our categorization of craniosynostosis surgery as a procedure with a low intrinsic surgical risk of mortality.…”
Section: Competing Interestsmentioning
confidence: 99%
“…More than 90% of craniofacial surgical procedures performed in children worldwide are associated with transfusion of blood products. 1,2 Intraoperative bleeding, measuring half to a whole a blood volume, is attributed to numerous factors, including accelerated fibrinolysis. 3 Anti-fibrinolytic agents are the most common effective pharmaceutical patient blood management (PBM) intervention.…”
Section: Editor's Key Pointsmentioning
confidence: 99%